2018
DOI: 10.1002/lom3.10296
|View full text |Cite
|
Sign up to set email alerts
|

Length–volume relationship of lake phytoplankton

Abstract: The shapes of phytoplankton units (unicellular organisms and colonies) are extremely diverse, and no unique relationship exists between their volume, V, and longest linear dimension, L. However, an approximate scaling between these parameters can be found because the shape variations within each size class are constrained by cell physiology, grazing pressure, and optimality of resource acquisition. To determine this scaling and to test for its seasonal and interannual variation under changing environmental con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 23 publications
1
0
0
Order By: Relevance
“…10 4 μm 3 ) in freshwaters. This finding is consistent with that of a previous study (Mittler et al, 2019) in which the authors investigated the length–volume relations for phytoplankton communities and found that the shape distribution of planktic algae shifts to the dominance of elongated and complex forms with increasing length. Our results also show agreement with that of Ryabov et al (2021), who studied unicellular elements of oceanic phytoplankton and found no tendency for elongation with increasing cell volume.…”
Section: Discussionsupporting
confidence: 93%
“…10 4 μm 3 ) in freshwaters. This finding is consistent with that of a previous study (Mittler et al, 2019) in which the authors investigated the length–volume relations for phytoplankton communities and found that the shape distribution of planktic algae shifts to the dominance of elongated and complex forms with increasing length. Our results also show agreement with that of Ryabov et al (2021), who studied unicellular elements of oceanic phytoplankton and found no tendency for elongation with increasing cell volume.…”
Section: Discussionsupporting
confidence: 93%